Rare Presentation of Unilateral Weakness, Involuntary Movements and Ataxia with Subcortical T2 Hypointensity in a Diabetic Patient: A Case Report - Venkatraman Indiran; Prabakaran Maduraimuthu (Case Reports in Radiology)
Subcortical T2 hypointensity on MRI is not a common finding. We present a case of subcortical T2 hypointensity in a diabetic patient, who was referred with weakness of left lower limb and involuntary movements and ataxia of the left upper limb. Lab reports confirmed the diagnosis of nonketotic hyperglycemia. It is rather important to identify subcortical T2 hypointensity which has only been recently found to be associated with nonketotic hyperglycemia. Early identification and prompt correction of blood sugar would help in alleviating the neurological symptoms.